(untitled) (Cadernos de Sociomuseologia, 2009)
Museum Training Institute: Kershaw House, 55 Well Street, Bradford, BD1 5PS Britain’s system of vocational training and qualifications has been undergoing a fundamental revolution in recent years. The single most important feature of this revolution is the concept of competence - the ability to perform to the standards required in employment. It is in recognition of this ability that National and Scottish Vocational Qualifications are awarded.